Analysis of the Interobserver Variability in Penile Length Assessment. (1st October 2015) - Habous, M.; Muir, G.; Tealab, A.; Williamson, B.; Elkhouly, M.; Elhadek, W.; Mahmoud, S.; Laban, O.; Binsaleh, S.; Abdelwahab, O.; Mulhall, J. P.; Veale, D.
ABSTRACT: Introduction: Many men seek penile augmentation treatments—a standard tool for their counseling is to inform them of what is "normal." Although some studies suggest good correlation between stretched and erect penile length, those that have measured stretched and erect length simultaneously have shown significant variability. Aim: To assess the accuracy of differing penile measurements with multiple observers. Methods: We recruited 201 adult men (mean age 49.6 years) who achieved full erection using intracavernosal injection. Main Outcome Measures: Penile measurements were taken by one of seven andrology specialists in a private, temperature-controlled (21°C, 72°F) environment. Stretched flaccid and erect length and circumference were measured. We analyzed the accuracy of each flaccid measurement using the erect measurements as a reference, for the overall patient population and for each observer. Results: The mean underestimate of length from stretched flaccid to erect was 2.64 cm (21.4%) and girth 2.27 cm (19.5%). Interobserver variability ranged from a mean underestimate of 16–27% (length) and 15–27% (girth). Conclusions: In this large, multicenter, multi-observer study of penis size, flaccid measurements underestimated erect size. It also seems likely that there is significant interobserver variability. We believe erect penis measurements should be used for men being considered for treatment of small penis anxiety.